Nodnol : The narrative of a voyage for scientific investigation into the antarctic regions, the discovery of Astrogee, a second satellite or new world, resting on the South Pole of our Earth, its exploration, its strange fauna and flora, its marvellous natural phenomena, its wonderful nations of civilized Quadrumana and its glorious population of perfect humanity - Cameron, Peter, 1852- (1900)
Bound manuscript from approximately 1900 by artist Peter Caledon Cameron, with 17 pen and ink drawings located at the end of the file. Peter Caledon Cameron (1852-1934) was born in England, and lived in Philadelphia around the turn of the 20th century.